2015
DOI: 10.1007/s00213-015-4068-x
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of the dopamine D1 receptor in the sensorimotor gating deficits induced by high-fat diet

Abstract: This is the first evidence that HFD can induce long-lasting deficits in sensorimotor gating through alteration of cortical levels of DA and its metabolites. Our data suggest that HFD-induced PPI deficits are related to altered D1R signaling and that D1R antagonists may have therapeutic effects on the deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, few studies have reported blunted or even reduced ASR in patients experiencing PTSD (Ornitz and Pynoos, 1989; Medina et al, 2001; Grillon and Baas, 2003) and in animal models of stress (Conti and Printz, 2003; Adamec et al, 2006; Beck et al, 2008). It is also likely that the dampened startle reactivity in the rats that consumed the WD is a result of competing interactions between the diet and traumatic stress, since high-fat diets alone can impair sensorimotor gating (Labouesse et al, 2013; Wakabayashi et al, 2015). Further, the blunted startle reactivity may imply alterations in sensory thresholds for eliciting ASR, motor deficits, and peripheral mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported blunted or even reduced ASR in patients experiencing PTSD (Ornitz and Pynoos, 1989; Medina et al, 2001; Grillon and Baas, 2003) and in animal models of stress (Conti and Printz, 2003; Adamec et al, 2006; Beck et al, 2008). It is also likely that the dampened startle reactivity in the rats that consumed the WD is a result of competing interactions between the diet and traumatic stress, since high-fat diets alone can impair sensorimotor gating (Labouesse et al, 2013; Wakabayashi et al, 2015). Further, the blunted startle reactivity may imply alterations in sensory thresholds for eliciting ASR, motor deficits, and peripheral mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the brain monoaminergic theory has been the prevailing hypothesis of anxiety, and is associated with altered brain functioning. It has been reported that DA and its metabolites, 3,4-dihydroxyphenylacetic acid and HVA, increase significantly in the cerebral cortex following a long-term HFD intake (Wakabayashi et al, 2015). Furthermore, it was also recently reported that a HFD was associated with sensitization of the DA mesolimbic pathway, with higher bursting activity of DA neurons and enhanced DA release, and greater expression of tyrosine hydroxylase and D2 receptors in the nucleus accumbens (Naneix et al, 2017).…”
Section: Chronic High-fat Diet-induced Anxiety-like Behaviors Are Weamentioning
confidence: 97%
“…For example, a chronic (3 months) HFD altered striatal and mesolimbic dopamine (DA) signaling in rodents (Davis et al, 2008;Sharma and Fulton, 2013). Additionally, another animal study reported that chronic HFD consumption for 10 weeks targeted the cortex of mice, and caused emotional disturbances via DA dysfunction, characterized by increased DA turnover (Wakabayashi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…High sugar and high fat foods have been shown to potently stimulate this pathway (Avena, Rada, Moise, & Hoebel, ; Del Parigi, Chen, Salbe, Reiman, & Tataranni, ; Kenny, ). Moreover, excessive consumption of junk foods evokes enduring changes in the dopamine signaling within regions involved in both reward processing and higher cognitive function (i.e., decision making): the nucleus accumbens (Rada, Avena, & Hoebel, ; Sharma, Fernandes, & Fulton, ; Naneix et al, ), the hippocampus (Kaczmarczyk et al, ; Krishna et al, ), and the PFC (Wakabayashi, Numakawa, Ooshima, Hattori, & Kunugi, ). As such, the increased drive toward engaging in rewarding behaviors in adolescents and a readily available source of highly palatable foods within the environment can potentiate over‐consumption of highly “rewarding” palatable junk food.…”
Section: Reward Signaling In Adolescence—implications For Feeding Behmentioning
confidence: 99%